What’s in a Theme? On the Nature of Variation - Roman Ivanovitch (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2012)
Most descriptions or taxonomies of variation suggest a conception of “theme” as a repository of elements from which the variations will select, emphasizing now one aspect, now another. When considered as a temporal phenomenon, however, a theme appears not as a static arrangement of “structural” elements, but instead stands in a complex and reciprocal relationship to the variations: it bequeaths to them a set of expectations about how they might proceed, and yet exists as a mutable collection of possibilities or potentialities to be activated and reshaped by the course of the variations themselves. The article explores some of the consequences of this temporal approach, highlighting the crucial role of the listener in apprehending variation, awareness of the balance struck by a variation between fidelity to the theme and self-sustaining coherence, and most importantly, the possibility for the flow of derivation in effect to reverse itself: for the variations to color the apprehension (the memory) of the theme. Drawing upon Beethoven’s “Diabelli” and Bach’s “Goldberg” Variations (among other illustrations), the article also assesses philosopher Nelson Goodman’s important treatment of variation. In keeping with the notion of variation as an environment that can lay bare habits of musical thinking occasionally obscured in more complicated settings, the essay seeks eventually to apply the insights developed within the variation genre beyond these boundaries; the slow movement of Mozart’s Piano Concerto in A, K. 488, is used as an example.